Propriocepcja w aspekcie medycyny sportowej - Stolarczyk, A.; Smigielski, R.; Adamczyk, G. (Medycyna sportowa, 2000)
Proprioception, together with accompanying neuromuscular feedback mechanisms, constitutes an important component of creating and maintaining functional stability of joints. Neuromuscular control and joint stabilisation are mediated primarily by the central nervous system. A multisite sensory input, originating from the somatosensory, visual and vestibular systems, is received and processed by the brain and spinal cord. The accumulated and processed information results in a conscious awareness of position and motion, unconscious joint stabilisation through protective spinal reflexes, and the maintenance of posture and balance. Clinical research aimed at determining the effects of articular injuries of musculo-skeletal origin, and of surgery and rehabilitation on joint proprioception, neuromuscular control and balance, has focused on the knee and ankle joints. Such studies demonstrated alterations in proprioception resulting from capsuloligamentous injuries, partial restoration of proprioceptive acuity following ligament reconstruction, and suggested beneficial proprioceptive changes resulting from comprehensive rehabilitation programmes.